TLR2 Arg677Trp Polymorphism Increases Susceptibility to Tuberculosis in Homozygous Wild Type Individuals - Yousaf, Nireeta; Maqsood, Safa; Khan, Shandana; Zaheer, Mamoona; Hanif, Muhammad Umair (Current Trends in OMICS, 2025)
Single nucleotide polymorphisms (SNPs) of Toll-like Receptors TLR2 and TLR4 have been associated with the susceptibility and severity of tuberculosis in different populations, worldwide. However, no such report is available about the Pakistani population. Genetic polymorphisms can be considered as markers for the likelihood of developing pulmonary tuberculosis. TLR family has a significant role in enhancing innate immunity which mediates the inflammatory reaction against a broad array of pathogens. TLRs are critical in determining immune response to mycobacteria by interacting with various bacterial molecular patterns. In this case-control study, genomic DNA from 100 patients and 100 controls were extracted. SNP genotyping of 6 SNPs, namely TLR2 NC_000004.12:g.153703800C>T, NP_001305716.1:p.Ser298Phe, NC_000004.12:g.153703946A>G, NP_001305716.1:p.Lys347Glu, NC_000004.12:g.153704936C>T NP_001305716.1:p.Arg677Trp, and NC_000004.12:g.153705165G>A, NP_001305716.1:p.Arg753Gln and TLR4, NC_000009.12:g.117713024A>G NP_612564.1:p.Asp299Gly, and NC_000009.12:g.117713324C>T, NP_612564.1:pThr399Ile were performed. with amplification refractory mutation system (ARMS) PCR. The results showed that out of the 6 above-mentioned SNPs, only NC_000004.12:g.153704936C>T (NP_001305716.1:p.Arg677Trp), C>C wild-type genotype has a statistically significant association with tuberculosis (p < 0.05). Although this genotype showed no significant association with bacillary load, which shows disease severity. Furthermore, no significant association was found between bacillary load and duration of symptoms. It was concluded that in the study population of newly diagnosed cases of TB, as well as the positive association of NC_000004.12:g.153704936C>T (NP_001305716.1:p.Arg677Trp) wild-type genotype with TB susceptibility, needs to be validated on a larger population.